Coexistence of an aberrant right subclavian artery and anomalous origins of bilateral vertebral arteries: A case report - Wu, Yihong (Medicine (Baltimore), 2021)
RATIONALE: Anatomical variations in aortic arch (AA) branching are not unusual. Generally, these variations are asymptomatic and are diagnosed incidentally. Here, we report a rare case of a middle-aged female patient with an aberrant right subclavian artery (ARSA) associated with anomalous origins of the bilateral vertebral arteries (VAs). PATIENT CONCERNS: The patient treated for urolithiasis complained of repeated dizziness for several years. DIAGNOSES: Echocardiography and computed tomography angiography (CTA) confirmed arterial variations. Moreover, mild stenosis was found in the left common carotid artery (LCCA), which was considered to be the cause of dizziness. INTERVENTIONS: Congenital anomalous arteries were not necessary to intervene urgently, but aspirin and atorvastatin were administered to prevent potential thrombosis attributed to vascular stenosis after completing the operation for urolithiasis. OUTCOMES: Whether the symptoms will be alleviated or not should be continuously followed up, and the patient may accept interventional therapy in the future if necessary. LESSONS: Here, we report the rare variation of AA branches and highlight the importance of preoperative vascular assessment in surgical or interventional procedures for the affected body regions.